-1(2n+3)=2(-4n+3)

Simple and best practice solution for -1(2n+3)=2(-4n+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1(2n+3)=2(-4n+3) equation:


Simplifying
-1(2n + 3) = 2(-4n + 3)

Reorder the terms:
-1(3 + 2n) = 2(-4n + 3)
(3 * -1 + 2n * -1) = 2(-4n + 3)
(-3 + -2n) = 2(-4n + 3)

Reorder the terms:
-3 + -2n = 2(3 + -4n)
-3 + -2n = (3 * 2 + -4n * 2)
-3 + -2n = (6 + -8n)

Solving
-3 + -2n = 6 + -8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '8n' to each side of the equation.
-3 + -2n + 8n = 6 + -8n + 8n

Combine like terms: -2n + 8n = 6n
-3 + 6n = 6 + -8n + 8n

Combine like terms: -8n + 8n = 0
-3 + 6n = 6 + 0
-3 + 6n = 6

Add '3' to each side of the equation.
-3 + 3 + 6n = 6 + 3

Combine like terms: -3 + 3 = 0
0 + 6n = 6 + 3
6n = 6 + 3

Combine like terms: 6 + 3 = 9
6n = 9

Divide each side by '6'.
n = 1.5

Simplifying
n = 1.5

See similar equations:

| x^2-7=-10 | | 86=2(5x+3) | | A+8/3=28 | | (x-10)^2/5=(9x)^1/5 | | 2(16-4x)+22=30 | | 8n-7/4=-1 | | (1/3)-(19/(4x))=(1/4)-(1/(6x)) | | 5(y-3)=-1(y+6) | | -10n+3(8+8n)=-6n(n-4) | | 4(1-5x)-5x(7x-2)= | | 125=-4(2+3x)-7x | | 250-Q^2=4Q | | 8(w+8)-(2+6w)=w | | 1/138(11x+9x)-13=19/345x | | 390/(5(7+6)) | | 1/3-19/(4x)=1/4-1/6x | | 7x+8-3=12 | | 3(2x-1)+(3/2)(3x+4)=1-4x | | 6/(x+7)=8/x | | 3x^2-8=40 | | -3+8=27 | | 0.03(x-6)+0.02(x-4)=5.24 | | 10n+3(8+8n)=6n(n-4) | | 2x+x-3=45 | | X-1=-1+3x | | 19+5-8*4/2= | | 2x^4+11x^2+15=o | | 6/x+7=8/x | | 8-7k+3=-10 | | -1(4x-5)=x | | 2(x-8)+7=5(x+2)-3x-1 | | 4f+g=-2f-14 |

Equations solver categories